ESMO Consensus Conference on malignant lymphoma: management of 'ultra-high-risk' patients. (19th June 2018) - Hutchings, M; Ladetto, M; Buske, C; de Nully Brown, P; Ferreri, A J M; Pfreundschuh, M; Schmitz, N; Balari, A Sureda; van Imhoff, G; Walewski, J; ,
Abstract: The European Society for Medical Oncology (ESMO) consensus conference on malignant lymphoma was held on 20 June 2015 in Lugano, Switzerland, and included a multidisciplinary panel of 25 leading experts. The aim of the conference was to develop recommendations on critical subjects difficult to consider in detail in the ESMO Clinical Practice Guidelines. The following areas were identified: (1) the elderly patient, (2) prognostic factors suitable for clinical use and (3) the 'ultra-high-risk' group. Before the conference, the expert panel was divided into three working groups; each group focused on one of these areas in order to address clinically relevant questions relating to that topic. All relevant scientific literature, as identified by the experts, was reviewed in advance. During the consensus conference, each working group developed recommendations to address each of the questions devised by their group. These recommendations were then presented to the entire multidisciplinary panel and a consensus was reached. This manuscript presents recommendations regarding the management of the following 'ultra-high-risk' situations: (1) early central nervous system relapse of diffuse large B-cell lymphoma, (2) primary refractory Hodgkin lymphoma and (3) plasmablastic lymphoma. Results, including a summary of evidence supporting each recommendation, are detailed in this manuscript. All expert panel members approved this final article.